Insect Species Composition in Local Durian Loji Plantation in Karawang, West Jawa - Sabrina, Hanifa Khansa; Siriyah, Siti Latifatus; Saputro, Nurcahyo Widyo Daru (Jurnal Biologi Tropis, 2025)
Durian (Durio zibethinus) belong to a popular fruits in Southeast Asia and is widely distributed across various regions, particularly in Indonesia. Karawang regency, as one of the part of west java province, is one of the producers of local durian, known as durian loji. Successful durian cultivation is influenced by various biotic factors, among which insect biodiversity plays a critical role in pollination, pest control, and nutrient cycling. However, comprehensive studies on insect diversity in durian agroecosystems, particularly in Karawang, remain scarce. This study aimed to explore the insect community structure within Loji durian plantations to provide baseline data on species composition and ecological roles. Field sampling was conducted using three methods: sweep nets for aerial insects, beating sheets for foliage-dwelling species, and pitfall traps for ground-active arthropods. A total of 29 insect morphospecies from 9 orders were identified, including Coleoptera, Hymenoptera, Diptera, Dermaptera, Orthoptera, Hemiptera, Odonata, Mantodea, and Lepidoptera. Our findings show that all morphospecies occupied various trophic levels, including herbivores, predators, and decomposers. These findings highlight the ecological significance of insects in maintaining durian plantation health and suggest the need for sustainable farming practices to conserve beneficial species while managing pests. Further research should investigate the seasonal variations and the impact of agricultural practices on insect community structure and diversity.